2023
DOI: 10.1007/s00280-023-04529-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potential of mitochondria-targeted antioxidant, mito-TEMPO, in 5-fluorouracil-induced cardiotoxicity

Abstract: Purpose The mitochondria-targeted antioxidants (MTAs) are known to offer protection against mitochondrial oxidative stress. The recent evidences support their role in mitigating oxidative stress-induced diseases, including cancer. Therefore, this study investigated cardioprotective potential of mito-TEMPO against 5-FU-induced cardiotoxicity. Methods Mito-TEMPO was administered to male BALB/C mice (intraperitoneally, 0.1 mg/kg b.w. for 7 days) followed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Studies have indicated that cardiotoxicity related to 5-FU may affect 1.5–21% of patients [ 2 , 4 ]. Drug-induced cardiac tissue injury might result from the over activation of several inflammatory signaling pathways [ 5 , 6 ]. Both oncology and cardiovascular disorders have increasingly focused on the systemic immune-inflammation index (SII).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that cardiotoxicity related to 5-FU may affect 1.5–21% of patients [ 2 , 4 ]. Drug-induced cardiac tissue injury might result from the over activation of several inflammatory signaling pathways [ 5 , 6 ]. Both oncology and cardiovascular disorders have increasingly focused on the systemic immune-inflammation index (SII).…”
Section: Introductionmentioning
confidence: 99%